A proposed model of dieting and nondieting in college women - Cohn, Meredith N., author; Rickard, Kathryn M., advisor; Zimmerman, Toni Schindler, committee member; Borrayo, Evelinn A., committee member; Swaim, Randall, committee member (Colorado State University. Libraries, 2006)
Given the pervasiveness of dieting in western culture and its link to eating disorders and other negative psychological and physiological states, the purpose of this study was to gain a better understanding of the factors that both predispose and buffer college-aged women from cosmetic dieting. A structural model was created to examine the influences of a number of psychological, sociocultural, familial, and intra- and interpersonal variables on dieting behavior. The sample consisted of 301 female, undergraduate college students enrolled in introductory psychology courses at Colorado State University. Data were analyzed in three stages. First, a series of MANOVAs were conducted to provide descriptive data on individual instruments and to test mean differences in model variables. Next, study instruments were entered in a confirmatory factor analysis (CFA) to determine the appropriateness of the proposed latent construct model. Finally, a structural model was tested predicting dieting status from the proposed latent constructs. Results from the MANOVA analyses illustrated that more frequent dieting was associated with greater awareness and internalization of appearance norms, lower perceived social support from peers, lower levels of assertiveness, greater conformity disposition, lower self-esteem, and greater body dissatisfaction. Surprisingly, family support was not related to dieting behavior. The MANOVA results suggested that the factors that posed the greatest risk were internalization of cultural messages and dissatisfaction with one's body. The final structural model specified that the relationship between self-esteem and dieting status was fully mediated by body dissatisfaction, which was also predicted by body mass index (BMI). Specifically, high self-esteem was predicted by high peer support, low adherence to norms for appearance, and low susceptibility to conformity. Subsequently, increases in self-esteem and reduction in BMI resulted in reduction of body dissatisfaction, which, in turn, predicted less frequent dieting. The model was considered an adequately-fitting model, and the final structural model accounted for 66% of the variance in dieting status. Discussion focused on the implications of these findings for developing treatment and prevention efforts for decreasing dieting in the college population.
Keywords: psychotherapy; health education; clinical psychology